The white Buddhist : the Asian odyssey of Henry Steel Olcott - Prothero, Stephen R. (Bloomington : Indiana University Press, 1996)
The New York Times denounced him as an "unmitigated rascal". Others described him as a reincarnation of the Buddhist emperor Ashoka or perhaps Gautama Buddha himself. He was Colonel Henry Steel Olcott (1832 - 1907), friend to Madame Blavatsky and president-founder of the Theosophical Society. This book tells the fascinating story of his spiritual odyssey. Raised a Presbyterian in nineteenth century New York, Olcott embraced spiritualism and then theosophy before becoming the first American of European descent to make a formal conversion to Buddhism. Despite his repudiation of Christianity, Olcott's life was an extension of both the "errand to the wilderness" of his Puritan ancestors and the "errand to the world" of American Protestant missionaries. Olcott viewed himself as a defender of Asian religions against the missionaries, but his actions mirrored theirs. He wrote and distributed tracts and catechisms, promoted the translation of scriptures into vernacular languages, established Sunday schools, founded voluntary associations, and conducted revivals. And he too labored to "uplift" his Asian acquaintances, urging them to embrace social reforms such as temperance and women's rights. However one views his work, his legacy was a lasting one, and today he is revered in Sri Lanka as a leader of the Sinhalese Buddhist Revival and in India as a key contributor to the Indian Renaissance.
1. Universal Reformer -- 2. From Spiritualism to Theosophy -- 3. An Errand to Asia -- 4. The Sinhalese Buddhist Revival -- 5. A United Buddhist World -- 6. The Indian Renaissance -- 7. Things Fall Apart.
Includes bibliographical references (pages 221-233) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Olcott, Henry Steel, -- 1832-1907.; Olcott, Henry Steel, -- 1832-1907; Umschulungswerkstätten für Siedler und Auswanderer; Buddhists -- United States -- Biography; Buddhists; United States; Buddhismus; Geschichte; USA; Buddhism; Religion; Philosophy & Religion; Buddhists -- United States -- Biography; Olcott, Henry Steel -- 1832-1907; Biographies